KUIS INTERAKTIF SEBAGAI MEDIA PEMBELAJARAN PENERJEMAHAN - Sari, Tanti Kurnia; Perdamean, Ahmad Sahat; Lubis, Nurhanifah (J-EDu: Journal - Erfolgreicher Deutschunterricht, 2025)
Following the Learning Outcomes of the Translation Course (Übersetzung), students are expected to be able to understand the concepts and theories of translation. For this reason, interesting learning media are needed to help students understand translation materials easily. This research aims to develop interactive quiz learning media for translation courses (Übersetzung). The development of learning media uses the Richey and Klein development model with three phases: the planning phase, the development phase, and the evaluation phase. The results of the study are interactive quiz learning media for the translation course with AhaSlide consisting of 90 slides, with 19 slides explaining the theme of translation techniques and 67 slides being exercises in the form of interactive quizzes totaling 45 questions. The interactive quizzes consist of three types of games, namely: 1) matching; 2) multiple choice, and 3) composing sentences. This interactive quiz learning media can be opened via online for lecturers as editors and for students as users. The learning media developed in this research is interactive media for translation learning, where media like this have not been developed before.